2018
DOI: 10.1016/j.eurpolymj.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of polystyrene- b -poly(2-vinylpyridine)- b -poly(ethylene oxide) triblock terpolymers

Abstract: Polystyrene-b-poly(2-vinylpyridine)-b-poly(ethylene oxide) (PS-b-P2VP-b-PEO)terpolymer is a versatile polymer to form isoporous films and membranes, due to the possibility of self-assembly control and the properties of the different blocks, such as the P2VP ability of complexation, and H-bond formation, and the PEO biocompatibility.Copolymers with different block ratios and sizes were synthesized. The correlation between their equilibrium bulk morphology, the self-assembly in dilute and semi-dilute solutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Influence of the order in solution. The self-assembly in the casting solution of block copolymer isoporous membranes has been confirmed in detailed by small-angle x-ray scattering static [68][69][70] and time-resolved experiments, pioneered by KAUST and Cornell groups. [71] Experiments have been later conducted by different groups.…”
Section: Self-assembly and Non-solvent Induced Phase Separation (Snips)mentioning
confidence: 90%
See 1 more Smart Citation
“…Influence of the order in solution. The self-assembly in the casting solution of block copolymer isoporous membranes has been confirmed in detailed by small-angle x-ray scattering static [68][69][70] and time-resolved experiments, pioneered by KAUST and Cornell groups. [71] Experiments have been later conducted by different groups.…”
Section: Self-assembly and Non-solvent Induced Phase Separation (Snips)mentioning
confidence: 90%
“…Even if in detail the interpretations might differ, the proposed relevance of the self-assembly in solution has been confirmed by all groups. [70,[72][73][74][75] By comparing a PS-b-P4VP diblock and the corresponding triblock copolymer with isoprene as the third block, it was observed that hexagonal or body centered cubic self-assembly in solution, as in Figure 5, were correlated to the same kind of pore arrangement in the membrane pore distribution. [68] Therefore not only the presence of order in solution is essential, but its kind.…”
Section: Self-assembly and Non-solvent Induced Phase Separation (Snips)mentioning
confidence: 99%
“…Table 1 summarizes the data on already reported linear triblock terpolymers in the literature [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], and, more specifically, block sequence, number (or weight) average molecular weight range and the annealing conditions used, together with the corresponding reference. It is straightf...…”
Section: Introductionmentioning
confidence: 99%
“…The shoulder signals at 3.0 to 3.3 ppm in the P (VDF‐ co ‐CTFE) spectrum are assigned to the proton on vinylidene fluoride (VDF) adjacent to CTFE (‐CF 2 ‐CH 2 ‐CFCl‐CF 2 ‐). Two additional signals appeared at 6.5 and 8.4 ppm, which are attributed to the grafting of P2VP segments onto P (VDF‐ co ‐CTFE) main chains . These signals are assigned to protons in the pyridine rings of P2VP side chains.…”
Section: Resultsmentioning
confidence: 97%
“…Two multiple signals were observed at 2.2 to 2.7 and 2.7 to 3.2 ppm, corresponding to the tail-tail (-CF 2 -CH 2 - ppm, which are attributed to the grafting of P2VP segments onto P (VDF-co-CTFE) main chains. 40,41 These signals are assigned to protons in the pyridine rings of P2VP side chains. As the content of P2VP increased, these two signals became more prominent.…”
Section: Table 2 Polymer Solution Composition For Membrane Fabricatiomentioning
confidence: 99%